PEMBUATAN MEDIA ALTERNATIF UNTUK PEMBELAJARAN GELOMBANG DAN OPTIK DI SMA KELAS XB SMA NEGERI 12 PEKANBARU - Nor, Muhammad; Sudrajat, Hendar; Awen, Husni Budi (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2007)
This research purpose to analyze effective usage of the media in the course of study and also know student response to usage of the appliance. This subject of the research was the students of XB Class of SMA 12 Pekanbaru consist of 44 students. Compiler data instrument in the form of the test result of learning to see the effectiveness of the appliance and questionnaire to know efficiency and also student response to the appliance. In analyzing data used by descriptive analysis and analysis usage of alternative media for thestudy of wave and optic in class XB. From data analysis obtained by usage of physics appliance effective enough where mean student absorption 74,70 %, while physic appliance efficiency resides in a high category with the mean score as a whole is 4,01. While the analysis of usage of media can be categorized is effective, although done by activity is the student cannot in perceiving directly, because of the limitation of time in study. So that more student work and can do experiments at home by teaming.